2008
DOI: 10.1093/aob/mcn106
|View full text |Cite
|
Sign up to set email alerts
|

Flower Morphology, Pollination Biology and Mating System of the Complex Flower of Vigna caracalla (Fabaceae: Papilionoideae)

Abstract: Self-fertilization may have evolved in the peripheral population at the highest site of V. caracalla because of the benefits of reproductive assurance under reduced pollinator diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 59 publications
0
45
0
22
Order By: Relevance
“…It could be considered that the founding of new populations strongly favors SC as described by Baker (1955), and that colonization with only one selfcompatible individual is possible in L. longiflorum because it produces several hundred seeds per flower. Reduced pollinator density (Etcheverry et al, 2008) and both reduced population size and isolation (Mimura and Arrken, 2007) often occurring at the periphery of the distribution area might promote a rapid evolutionary shift to self-fertilization, and eventually to selfing in a colonizing population. Hiramatsu et al (2001a) stated that L. formosanum is regarded as a recent derivative species from some L. longiflorum populations in the southern Ryukyu Archipelago group.…”
Section: Multiple Origins Of Self-compatible Populationsmentioning
confidence: 99%
“…It could be considered that the founding of new populations strongly favors SC as described by Baker (1955), and that colonization with only one selfcompatible individual is possible in L. longiflorum because it produces several hundred seeds per flower. Reduced pollinator density (Etcheverry et al, 2008) and both reduced population size and isolation (Mimura and Arrken, 2007) often occurring at the periphery of the distribution area might promote a rapid evolutionary shift to self-fertilization, and eventually to selfing in a colonizing population. Hiramatsu et al (2001a) stated that L. formosanum is regarded as a recent derivative species from some L. longiflorum populations in the southern Ryukyu Archipelago group.…”
Section: Multiple Origins Of Self-compatible Populationsmentioning
confidence: 99%
“…Brito et al (2010) studied the reproductive biology of other Fabaceae species and also reported high pollen viability: 97% in Sophora tomentosa and 99% in Crotalaria vitellina. According to Etcheverry et al (2008), the flowers of Fabaceae species show an intricate architecture. Therefore, pollen reception can only be achieved by highly specialized mechanisms.…”
Section: Characteristics Of the Speciesmentioning
confidence: 99%
“…Las características y la disposición de sus piezas constituyen un carácter de importancia taxonómica y su función estaría relacionada con el almacenamiento y protección del néctar en la flor (Rodríguez Riaño et al, 1999b). Además, el cáliz tiene importancia durante el movimiento de la corola, evitando la desarticulación de las piezas durante las visitas de los insectos (Etcheverry et al, 2003(Etcheverry et al, , 2008Le Roux & Van Wyk, 2012). La corola también es pentámera y dialipétala, generalmente con un pétalo más desarrollado que el resto de las piezas florales, llamado estandarte o vexilo (Westerkamp & Weber, 1999;Tucker, 2003).…”
Section: Introductionunclassified
“…Durante la antesis, el estandarte generalmente actúa como un órgano de atracción para los polinizadores (Arroyo, 1981;Tucker, 2003), y puede presentar guías de néctar, ya sea táctiles y/o visuales (e.g. Etcheverry et al, 2008). Las alas son piezas que pueden tener tres funciones (excepto en las flores ornitófilas): (1) atracción, (2) lugar para posarse los insectos y (3) palancas que deprimen y elevan a la quilla en el momento de la polinización a través del complejo alas-quilla (Stirton, 1981;Westerkamp, 1997;Etcheverry, 2001aEtcheverry, , 2001bEtcheverry et al, 2003;Alemán et al, 2014).…”
Section: Introductionunclassified
See 1 more Smart Citation